IN VITRO ANTIBACTERIAL AND ANTIFUNGAL ACTIVITIES OF AQUEOUS AND ETHANOLIC LEAF EXTRACTS OF ACACIA AURICULIFORMIS - Shobha Rao, Amita; Kl, Shobha; S Shetty, Manjunath; R Pai K, Sreedhara (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study focuses on in vitro antimicrobial properties of aqueous and ethanol leaf extract of Acacia auriculiformis tested on Gram-positive cocci, Gram-negative bacilli, multidrug-resistant (MDR) Gram-negative bacilli, and fungus. Methods: Ethanol and aqueous extracts of the leaves of A. auriculiformis were prepared. Agar well diffusion was the method for antimicrobial susceptibility. Freshly grown standard strains of Staphylococcus aureus, Enterococcus faecalis, Klebsiella pneumoniae (K. pneumoniae) , Escherchia coli (E.coli) and Pseudomonas aeruginosa, clinical strains of Streptococcus pneumoniae, Candida albicans (C. ailbicans), and MDR E. coli, and MDR Klebsiella pnuemoniae were used. Ampicillin disc (10 Î¼g) was used as control. Results: The zone of inhibition was measured to determine the antimicrobial activity. Ethanolic extract of A. auriculiformis exhibited antibacterial activity against all the strains including MDR strains of K. pneumoniae and E. coli. Antifungal activity was exhibited by both aqueous and ethanol leaf extracts of A. auriculiformis. Conclusion: Ethanol extract could be used against MDR K. pneumoniae and MDR E. coli. Similarly, aqueous and ethanol extract can be the drug of choice for C. albicans infection. Further study is necessary to evaluate the accurate compound responsible for antibacterial and antifungal activity for pharmaceutical applications.